Selected applications of Er:YAG and CO2 lasers for treatment of benign neoplasms and tumorous lesions in the mouth - Błochowiak, Katarzyna; Andrysiak, Piotr; Sidorowicz, Krzysztof; Witmanowski, Henryk; Hędzelek, Wiesław; Sokalski, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Benign neoplasms and hyperplastic tumorous lesions are common oral pathologies. These lesions require to be surgically removed by conventional surgery, laser, or electrosurgery. Surgical treatment aims at complete removal of pathological lesions and ensuring proper healing of the tissues to minimize the risk of lesion recurrence. Aim: To present possible applications of Er:YAG and CO 2 lasers in removal of benign neoplasms and tumorous lesions developing on oral mucosa as well as to specify indications and limitations of these two methods. Material and methods: Temperature-induced injuries due to laser light application, possibility of post-operative histopathological evaluation of the removed tissue, efficacy of the cut and coagulation, healing process and completeness of laser surgeries give rise to our special concern. Results : The main asset of the CO 2 laser comparing to Er:YAG laser is an effective coagulation while thermal injury to the tissues is its limitation, especially with multiple passage of the beam and too high power applied. Er:YAG laser application does not exclude histopathological examination of the removed lesion tissue which is its advantage over CO 2 laser. Conclusions : Still, insufficient coagulation is a limitation ofits use in the case of richly vascularized lesions.